Case report: The use of biodegradable temporising matrix in breast reconstruction following flame burn to chest - S. Telianidis; D. Reilly; D. Holden; H. Cleland (Elsevier, 2020)
Biodegradable Temporising Matrix (BTM) has shown excellent functional results following complex full thickness burns to the limbs, however there is limited literature in BTM use in breast reconstruction post burns. This is a case report of a patient who sustained 36% total body surface area (TBSA) burns, including full thickness burns to bilateral breasts, following a house fire. Following initial debridement, BTM was placed on day two of admission. The breast contour and three-dimensional structure was maintained by using a bra-shaped covering of BTM. On day 36, the BTM was delaminated and autologous split skin grafts were placed. There were small areas of graft loss (1% TBSA) secondary to infection, which required further re-grafting. This case is unique in that BTM was applied in the acute burn injury setting. This technique and timing of BTM placement is was shown to be advantageous in our case as contractures of the breast tissue were minimal, and we were able to maintain normal breast anatomy. Future studies should explore the validity of this novel technique in acute management of full thickness burns to breasts.